The Legal Challenges In Using Vessel Protection Detachment and Their Functional Immunity - Putri, Putu Ayu Dinda Paramita Selamet; Utari, Anak Agung Sri (Kertha Patrika, 2019)
On February 15th 2012, the St. Antony, an Indian fishing boat, was fired by a passing ship, MT Enrica Lexie, in the Exclusive Economic Zone (EEZ) of India. The boat was fired by Vessel Protection Detachment (VPDs), Italian trained Navy personnels that were assigned to protect Italian maritime interest against piracy. This case has been long-disputed by Indian and Italian government because the fired happened in the Indian EEZ  where India declares to have criminal jurisdiction. A serious concern also raised due to the deployment of Italian VPD which Italy considered as a State organ that is granted with functional immunity, onboard commercial vessel. This article is aimed to analyze the function of VPD in protecting the ship from piracy and the existence of functional are in international law by normative legal research. The challenges of using VPDs are while they are operating onboard a commercial vessel and sailing through territorial waters of some coastal states since the embarkation of armed military personnel on privately owned and operated vessels could diminish the merchant vessels’ status under the right of innocent passage. The functional immunity of Italian VPD is still questioned, based on their status as a State organ and their conduct in this case as an “official” or “private” conduct.